(untitled) (Journal of Hama University, 2020)
The nature of leukemia and its different treatments may be the same for all patients, but the difference in patients’ reactions, how they respond to the infection and how they correspond to it, from is the beginning and entering into symptoms, is determined by several factors that vary from patient to patient, The ability of the patient to be successful Compatibility depends on the experience gained from the family and society in general, as well as on the extent of success in building a positive self-esteem and appreciation of them, so this descriptive study aimed to identify the level of educational needs of patients with leukemia 50 adult patients with leukemia in Lattakia were selected by the convenient sample method. The data were collected using a questionnaire developed by the researcher. The study showed that 60% of patients have a high level of learning needs associated with symptoms, and that 60% of them have an average level of learning needs associated with the axis of physical activity, and 50% of them have an average level of learning needs associated with diet. The study recommended the development of educational programs for patients with leukemia, to increase their knowledge about leukemia, its treatment and diet, so that these programs involve patients and their families